Exogenous spraying of plant's resistance inducers improves yield and sugarcane quality - Viana, Ronaldo da Silva [UNESP]; Almeida Moreira, Bruno Rafael de [UNESP]; Manzani Lisboa, Lucas Aparecido [UNESP]; Monteiro de Figueiredo, Paulo Alexandre [UNESP]; Ramos, Sergio Bispo [UNESP]; Ramos, Samuel Bispo [UNESP]; Oliveira Dias, Gustavo Henrique de; Moreira, Leticia Cunha; Spotoni, Mariana Teixeira; Silva Baleroni Recco, Camila Regina (Scientific Issues Natl Centre Agrarian Sciences, 2019)
Sugarcane crop is important to sugar-energy industry. Thus, the aim of this study was to evaluate yield and technological quality of Sugarcane juice obtained from the SP81-3250 variety following exogenous spraying of resistance inducers. The experiment consisted of a randomized block design with four replicates per treatment: salicylic acid (0, 5, 10, 20, and 40 mu M) and acibenzolar-S-methyl (0, 0.2, 0.4, 0.8 and 1.6 g 100 L-1). The resistance inducers were sprayed using CO2-pressurized sprayer. Sugarcane tillage was harvested thirty-days after the spraying of resistance inducers and stalks were milled for juice samples extraction, in which were evaluated the following parameters: degrees Brix, Pol, purity, reducing sugars (RS), total reducing sugars (TRS), theoretical sugar recoverable (TSR), fibres and yields of sugar and stalks. Obtained data was submitted to following statistical tests (P < 0.05): Shapiro-Wilk's normality, Fisher's variance, regression, and Pearson's linear correlation. Results showed that quadratic trends rejected null hypothesis for almost all parameters. Salicylic acid levels till 10 mu M increased degrees Brix, Pol, purity, TRS, TSR contents and sugar and stalks yield. However, 20 and 40 mu M showed negative effects on juice technological quality and agronomic performance. Therefore, the elicitors improved photosynthetic characteristics and sugarcane physiological maturation. It was concluded that salicylic acid and acibenzolar-S-methyl levels till 10 mu M and 0.8 g 100 L-1, respectively, are recommendable to management of SP81-3250 variety.
Keywords: acibenzolar-S-methyl; phytohormones; plant resistance; inducers; salicylic acid; Saccharum spp.